Implementation of Legal Protection for Patients in Drug Processing Based on Doctor's Prescription by Pharmacies (Case Study of Decision Number 2258/PID.SUS/2020/PN MDN) - Haryono, Tri Agus; Rosidah, Rosidah; Permana, Diki; Bunyamin, Bubun; Yuliarpan, Pipit; Wiradirja, Imas Rosidawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to analyze the implementation of legal protection for patients in the processing of drugs based on doctor's prescriptions by pharmacies, focusing on the case study of Decision Number 2258/PID.SUS/2020/PN MDN. Through a qualitative approach, this research explores the legal aspects that protect patients as well as the challenges faced in the practice of implementing drug prescriptions. The results show that despite clear regulations, there are still loopholes in their implementation that can harm patients. Greater efforts are needed to improve supervision of the drug processing process, including through regular inspections and training related to health law. This research shows that legal protection for patients in the context of drug processing by pharmacies is still a complex issue that requires greater attention from various relevant parties.